Design and Simulation of Secondary Acceleration Type Rotor for Vertical Shaft impact Crusher - Wu, Canhui; Zhao, Limei; Zhang, Cheng (Manufacturing Technology Journal, 2024)
In order to improve the crushing effect of the rotor of vertical shaft impact crusher on the particle, the design method of secondary accelerated rotor based on kinematics theory is proposed. And the operation effect of the secondary acceleration type rotor was verified using a combination of computational fluid dynamics and discrete element method (CFD-EDM). First, the kinematics of the particles thrown by the rotor throwing head was analyzed. On this basis, the structure of the secondary acceleration type rotor was designed by comprehensively considering factors such as the motion, friction, and collision recovery coefficient of particles; Then, based on the gas-solid coupling analysis method, a simulation model of the rotor's effect on particle acceleration was established and the reliability of the model was verified; Finally, the CFD-EDM method was used to calculate and analyze the motion process of particles in the crushing chamber, the collision position of particles in the crushing chamber, and the average throwing speed of the rotor. Research results show that roughly 77.6% of the particles in the crushing chamber will collide with the impact plate to achieve secondary acceleration; The average throwing speed of the traditional rotor is 57.14m/s, and the average throwing speed of the designed secondary accelerated rotor is 60.89m/s, which is about 6% higher than the average throwing speed compared with the traditional rotor, and achieves the expected design purpose.
Keywords: Vertical shaft impact crusher; Secondary accelerated rotor; Kinematic analysis; CFD-DEM